2015
DOI: 10.4236/wjnse.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Production of Silver Nanoparticles from Peel of Tangerine for Degradation of Dye

Abstract: Green chemistry methods for production of nanoparticles have many advantages, such as ease of use, which makes the methods desirable and economically viable. The aim of the present work was to green synthesise silver nanoparticles (SNPs) using aqueous tangerine peel extract in different ratios (2:1, 1:1, 1:2). The formed SNPs were characterised using ultraviolet-visible (UV-Vis) spectrophotometry, and transmission electron microscopy (TEM). The UV-Vis spectra showed that the highest absorbance was observed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Formation of Green AgNPs. For use in analytical applications, stable silver nanoparticles should be synthesized against the dilution, over ionic strength, different pH ranges, and long storage period [28,48,52]. In this study, wetchemical green synthesis was used for preparing the green silver nanoparticles because it constituted the most prevalent procedure for fabricating uniform nanoparticles with regulated sizes and strong silver nanoparticles alongside their colloidal dispersions in organic solvents or water [54][55][56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of Green AgNPs. For use in analytical applications, stable silver nanoparticles should be synthesized against the dilution, over ionic strength, different pH ranges, and long storage period [28,48,52]. In this study, wetchemical green synthesis was used for preparing the green silver nanoparticles because it constituted the most prevalent procedure for fabricating uniform nanoparticles with regulated sizes and strong silver nanoparticles alongside their colloidal dispersions in organic solvents or water [54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…Significant research attention in the development of mercury sensors has been accorded to AgNPs, particularly because of soft-soft chemistry involving sulfur with stabilizing ligands on AgNPs surfaces, thus changing the peak position and absorbance intensity, the presence of redox chemistry involving AgNPs (Ag°) and Hg 2+ leading to formation of Ag − Hg mixture through nanoparticle etching, high sensitivity of AgNPs localized surface plasmon resonances, and cost-effective synthesis [2]. Besides, a UV − Vis spectrophotometer containing specific optical properties and which use LSPRs within the visibility range of 350-800 nm can be used for easy monitoring of AgNPs [26][27][28][29][30][31]. Radiation chemical reductions [32], photo reduction within reverse micelles [33], and chemical stabilisation with reagents, including sodium borohydride, ascorbate, and sodium citrate [34][35][36][37] have been used for synthesizing silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…8,52 Figure 2 shows the TEM micrographs of the fabricated Acacia gum–stabilised SNPs, using different magnifications. It was observed that the fabricated SNPs were in the nano range and were well dispersed without aggregation, possessing a spherical shape.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Silver nanoparticles can be monitored using a ultraviolet-visible (UV-Vis) spectrophotometer with specific optical characteristics using localised surface plasmon resonance (LSPR) in the visible range (350-800 nm). 68 …”
Section: Introductionmentioning
confidence: 99%
“…A large amount of the researches based on different methods of developing and synthesizing nanoparticles are reported in the literature [32][33][34][35]. Magnetic nanoparticles are essentially nanoparticles that can be manipulated using a magnetic field.…”
mentioning
confidence: 99%